Synthesis and some properties of hybrid gels of titanium oxide containing europium (III) - Calefi, Paulo S.; Nassar, Eduardo J. [UNESP]; Neri, Cl áudio R.; Serra, Osvaldo A. (Elsevier B.V., 1999)
In this work, we report the synthesis and properties of TiO2 and of an organic-inorganic hybrid of TiO2 where the inorganic network was obtained by hydrolysis (sol-gel process) of the titanium tetraisopropoxide precursor. Both materials were prepared and dried in air. The organic oligomer was synthesized by esterification between ethylene glycol and dipicolinic acid, using Eu3+ as probe. These materials were studied by luminescence and infrared spectroscopies, thermogravimetric analysis and X-ray diffraction. The results obtained for the hybrid material show the formation of two crystalline polymers. Eu3+ has been used as structural probe due to its photophysical properties and also as emission center for luminescent materials and the luminescence data indicate that Eu3+ occupies one kind of site that is isolated from water molecules and OH groups. (C) 1999 Elsevier B.V. B.V. All rights reserved.